2000
DOI: 10.1182/blood.v95.10.3085
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transduction of human hematopoietic repopulating cells generating stable engraftment of transgene-expressing cells in NOD/SCID mice

Abstract: In an attempt to develop efficient procedures of human hematopoietic gene therapy, retrovirally transduced CD34+ cord blood cells were transplanted into NOD/SCID mice to evaluate the repopulating potential of transduced grafts. Samples were prestimulated on Retronectin-coated dishes and infected with gibbon ape leukemia virus (GALV)-pseudotyped FMEV vectors encoding the enhanced green fluorescent protein (EGFP). Periodic analyses of bone marrow (BM) from transplanted recipients revealed a sustained engraftment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Similar results have been reported in the hematopoietic system, another rapidly renewing tissue. In these studies, the clonal make-up of transduced human hematopoiesis-engrafting NOD/SCID mice was demonstrated to occur also at the expense of a discrete number of clones (Barquinero et al, 2000;Güenechea et al, 2001). The loss of polyclonality and emergence of a small number of clones strongly suggest in vivo selection for epidermal stem cells with extended growth capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in the hematopoietic system, another rapidly renewing tissue. In these studies, the clonal make-up of transduced human hematopoiesis-engrafting NOD/SCID mice was demonstrated to occur also at the expense of a discrete number of clones (Barquinero et al, 2000;Güenechea et al, 2001). The loss of polyclonality and emergence of a small number of clones strongly suggest in vivo selection for epidermal stem cells with extended growth capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In the remaining mice there was an overall increase in EGFP‐expressing cells. Recently, Barquinero et al also observed a decline in EGFP expression in a small cohort of mice that they attributed to gene silencing 19. Second, assessment of the proportion of human cells containing integrated provirus revealed the same patterns of repopulation kinetics as with EGFP expression.…”
Section: Discussionmentioning
confidence: 91%
“…Our original studies indicated that SRCs from cord blood (CB) are difficult to transduce with retroviral vectors (only 50% of transplanted mice contained 0.1% to 3% transduced human cells) 13. Subsequently, we and others have optimized the transduction procedure both for transduction efficiency and the maintenance and/or expansion of functional repopulating cells 14–19. Human bone marrow‐derived SRCs are still transduced with low efficiency under these conditions, which points to major differences in CB and BM‐derived SRCs.…”
Section: Optimized Gene Transfermentioning
confidence: 99%
“…Cord blood CD34+ cells have been transduced successfully with a range of viral vectors bearing a variety of markers (Schilz et al, 1998;Conneally et al, 1998;Miyoshi et al, 1999;Woods et al, 2000;Guenechea et al, 2000;Barquinero et al, 2000;Abonour et al, 2000;Salmon et al, 2000). Primitive cord blood cells are favourable as they have greater transduction efficiency in comparison to similar cells from the bone marrow.…”
Section: Gene Therapymentioning
confidence: 99%